2013
DOI: 10.1371/journal.pone.0068905
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Inhibits Lipopolysaccharide-Stimulated Rheumatoid Fibroblast-Like Synoviocyte Invasion through Suppression of TLR4/NF-κB-Mediated Matrix Metalloproteinase-9 Expression

Abstract: Invasion of fibroblast-like synoviocytes (FLSs) is critical in the pathogenesis of rheumatoid arthritis (RA). The metalloproteinases (MMPs) and activator of Toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) pathway play a critical role in RA-FLS invasion induced by lipopolysaccharide (LPS). The present study aimed to explore the anti-invasive activity of celastrol on LPS-stimulated human RA-FLSs, and to elucidate the mechanism involved. We investigated the effect of celastrol on LPS-induced FLS migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 35 publications
4
61
0
Order By: Relevance
“…We also noted that the number of the α-SMA + CMFs was reduced in the colonic mucosa of these knockout (KO) mice. This may be due to the reduced MyD88-dependent fibroblast migration and differentiation as has been noted in the small intestine and other organs (22, 53). However, the α–SMA + positive cells (a.k.a.…”
Section: Resultsmentioning
confidence: 90%
“…We also noted that the number of the α-SMA + CMFs was reduced in the colonic mucosa of these knockout (KO) mice. This may be due to the reduced MyD88-dependent fibroblast migration and differentiation as has been noted in the small intestine and other organs (22, 53). However, the α–SMA + positive cells (a.k.a.…”
Section: Resultsmentioning
confidence: 90%
“…It has been reported that the translocation and subsequent DNA binding of NF-κB in inflamed synovium transactivates [42,53] . Therefore, NF-κB has been extensively studied to determine its role in the pathogenesis of RA, and NF-κB inhibition has been explored as a therapeutic approach to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…RA FLSs have the ability to secrete zinc-dependent proteases such as MMPs, which promote degradation of the extracellular matrix proteins in joints and bones [41] . MMP-9, also called collagenases, are induced in RA FLSs by pro-inflammatory cytokines and LPS [3,42] . A recent report suggests that MMP-9 plays an important role in RA FLS migration and invasion induced by LPS [42] .…”
Section: Effect Of Hyperoside On Lps-induced Production Of Pro-inflammentioning
confidence: 99%
See 1 more Smart Citation
“…Celastrus and various of its defined constituents possess anti-cancer, anti-inflammatory and anti-oxidant properties (18). Our previous studies demonstrated that the ethyl acetate extract of Celastrus orbiculatus (COE) has significant anti-tumor effects in vitro and in vivo (1,3,4,912). COE induced cytotoxicity and promoted the apoptosis of human hepatocellular carcinoma cells by inhibiting the Akt signaling pathway (9), and inhibited tumor angiogenesis by modulating the vascular endothelial growth factor signaling pathway (10).…”
Section: Introductionmentioning
confidence: 99%